Evaluasi Penerimaan Sistem Perencanaan dan Penilaian Anak Didik menggunakan Technology Acceptance Model - Muhammad Alkaff; Muti'a Maulida; Arina Ihda Rahmah Syarifah (Universitas Multimedia Nusantara, 2021)
Most teachers have difficulty in developing Learning Implementation Plans (RPP) due to the large number of instruments in the RPP that need to be made and adapted to the standard format. Likewise, when evaluating students, teachers need to look back at the lesson plan before conducting an assessment. Teacher activities in making lesson plans and assessing according to lesson plans are very time-consuming. Therefore, the Learning Planning and Assessment System for Students (SPADIK) was developed. This new application aimed to ease teacher effort in making learning plans and assessments for students at TK Khalifah Banjarmasin II. The teacher always welcomes the existence of new technology that can help their work. However, if the teacher cannot operate this new technology, they will certainly be in vain. Therefore, evaluation of acceptance of the SPADIK system is required by using the Technology Acceptance Model (TAM). This study uses a qualitative approach by conducting interviews with six kindergarten teachers of Khalifah Banjarmasin II, where this system was implemented. Data from interviews with teachers then reduced to a short description following the variables in the TAM model. From the results of testing with the TAM model, it was concluded that SPADIK could be accepted and used well by the teachers. Index Terms—evaluation; information system; RPP; students assessment; Technology Acceptance Model (TAM)